Proceedings of the 1st Aceh International Dental Meeting (AIDEM 2019), Oral Health International Conference on Art, Nature and 2021
DOI: 10.2991/ahsr.k.210201.019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Geothermal and Non-Geothermal Laban Plant (Vitex Pinnata) With a Combination of Infrared Spectroscopy – Principal Component Analysis Methods

Abstract: The purpose of this study is to identify laban leaf which originates from Ie Seu'um, Gunung Paro, and Lambaro, with a combination of Spectroscopy Fourier Transform Infrared (FTIR) and Principal Component Analysis (PCA) methods. FITR spectrum pattern from each sample was identified as multivariate using PCA and classified based on similarity or variety of the spectrum. The PCA analysis results of laban leaf samples are separated and forming both good groups as well as diversity percentage which is 96%. The extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Geothermal manifestations offer advantages in the energy field and extend their benefits to other domains, including pharmaceuticals [13][14][15][16]. These manifestations involve releasing reservoir geothermal fluids to the surface through permeable zones or cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal manifestations offer advantages in the energy field and extend their benefits to other domains, including pharmaceuticals [13][14][15][16]. These manifestations involve releasing reservoir geothermal fluids to the surface through permeable zones or cracks.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of C. gigantea in the textile and medicinal industries described above depended significantly on its secondary metabolites. The diversity and quantities of secondary metabolites depend on where the plant grows and how it grows, such as the temperature, the soil quality, the intensity of sunlight, and the volume of water available [22][23][24]. The ability of plants to survive and adapt in severe environments, such as geothermal zones, will improve the uniqueness of the secondary metabolites produced [23].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and quantities of secondary metabolites depend on where the plant grows and how it grows, such as the temperature, the soil quality, the intensity of sunlight, and the volume of water available [22][23][24]. The ability of plants to survive and adapt in severe environments, such as geothermal zones, will improve the uniqueness of the secondary metabolites produced [23]. Several studies have also been reported evaluating the benefits of C. gigantea from the geothermal manifestation area of Mount Seulawah Agam.…”
Section: Introductionmentioning
confidence: 99%